Traditional resource management and biocultural conservation: A case study for the relationship between Tombstone Territorial Park, the Tr'ondek Hwech'in and caribou - Heffner, Susan (Author); Shultis, John (Thesis advisor); Booth, Annie (Committee member); Rahemtulla, Farid (Committee member) (University of Northern British Columbia, 2018)
Biocultural approaches to conservation include the protection and appreciation of other ways of knowing the environment. Studies in traditional resource management systems illuminate the intricate ways culture has coevolved with nature and provide opportunities to incorporate alternate perceptions of the environment into conservation objectives. This thesis examines how traditional resource management systems contribute to biocultural conservation using a case study for the relationship between Tr’ondëk Hwëch’in First Nation, caribou and Tombstone Territorial Park. Core beliefs about the natural world, including caribou, are central to the strategies Tr’ondëk Hwëch’in employ in resource management. While cultural values and First Nation rights are engrained in park management, a broader understanding of how Tr’ondëk Hwëch’in know the natural world is lacking. Biocultural Resource Management Systems Conservation caribou Tombstone Territorial Park First Nations